The Correlation Between Nurse Motivation and Compliance in The Implementation of Fall Risk Prevention - Rina Rahmadani Sidabutar; Budiana Yazid (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Fall is a serious problem and requires high costs for patients and also for all wellness facilities. Morse Fall Score (MFS) was one of the assessments of risk of falls prevention efforts which was one of the principles of ability and behavior of nurses in doing work appropriate duties related to compliance implementation Standard Operating Procedures (SOP). One of the factors that influence nurse compliance in the implementation of SOP i.e. motivation and perceptions of nurse against their work. Motivation was one of the important things for someone in doing forefront where increasing motivation will lead to increased performance of nurses. This study aimed to know the correlation between the motivation of nurses and the implementation compliance of standard operating procedures of the risk of fall prevention inpatient care. This study used approach cross-sectional, non- probability sampling method that was purposive sampling. Statistical analysis used Spearman Rank tests with the significance value is 95% (α = 0.05). There was a significant correlation between the motivation of nurses with the standard operating procedures of implementation's compliance with the risk of fall prevention in the space of hospitalization with a p-value of 0.000 (p-value < 0.05). The correlations value (r) was 0.042 meaning forms two variable correlations were unidirectional i.e. the higher the motivation then the standard operating procedures of the implementation's compliance with the prevention of the risk of falling was also higher. There was a significant correlation between the motivation of nurse with compliance the implementation of standard operating of the risk of fall prevention in patient room. Keywords : Compliance, Motivation, Risk of fall, Standard Operating Procedure